Realizing Favorable Synergism Toward Efficient Hydrogen Evolution Reaction with Heterojunction Engineered Cu7S4/CuS2/NiS2 and Functionalized Carbon Sheet Heterostructures - Hemanth Kumar Beere; Srimanta Pakhira; Prahlada Thippeswamy; Ashok Singh; Shrish Nath Upadhyay; Pooja B. Naik; Nataraj Sanna Kotrappanavar; Debasis Ghosh (Advanced Materials Interfaces)
Abstract Electrochemical hydrogen generation via water splitting is the greenest approach toward the hydrogen economy. To satisfy the practical utilization, the electrocatalyst for hydrogen evolution reaction (HER) must be of low cost with high catalytic activity. Accordingly, transition metal based electrocatalysts have attracted significant research interest. Herein, this work demonstrates an efficient HER electrocatalyst based on copper nickel sulfide (CNS), and Agaricus bisporus biomass derived functionalized carbon (FMCs) based nanocomposites, where the CNS are in situ hydrothermally grown in presence of FMCs.  First, the effect of solvent (water, ethylene glycol, and glycerol) on the phase and crystallinity of CNS and their performance as HER electrocatalyst in acidic medium are demonstrated. The CNS heterojunction synthesized in aqueous medium (CNSW) shows the best HER catalytic activity with 269 mV (at 10 mA cm−2) overpotential and corresponding Tafel slope of 146.86 mV dec−1. Further, while the FMCs possess no catalytic activity itself, its control presence in the nanocomposites CNSW/FMCs nanocomposites caused a dramatic reduction in the HER overpotential (180 mV@10 mA cm−2) and the corresponding Tafel slope (78.71 mV dec−1). Notably, where the nonlayered metal sulfides generally are unstable in acidic medium, the synergistic interaction between the CNSW and FMCs enables stable catalytic activity for the measured 10 h.